AB0780 Secukinumab sustains individual clinical responses over time in patients with psoriatic arthritis: 2-year results from a phase 3 trial, future 2. (15th June 2017) - Emery, P; McInnes, IB; Mease, PJ; Schiff, M; Pricop, L; Shen, S; Wang, Z; Gaillez, C; ,
Abstract : Background: Achieving sustained clinical response to biologics is part of treat-to-target recommendations in psoriatic arthritis (PsA) and is aimed at optimising treatment goals. 1 Objectives: To evaluate patient (pt)-level secukinumab data and report the likelihood of improving, sustaining or worsening of American College of Rheumatology (ACR) response and disease status (disease activity score 28 based on C-reactive protein [DAS28-CRP]) from Week (Wk) 24 to 104 in pts with active PsA from the FUTURE 2 trial. 2, 3 Methods: The findings of the FUTURE 2 trial through Wk 104 have been previously reported. 3 Post-hoc shift analyses were performed on ACR response between Wks 24 and 104 for subgroups of secukinumab-treated pts, based on their higher response rate at an earlier time point in 1 out of 4 categories (ACR non-responders [NR], ACR20, 50 or 70) by evaluating whether the response improved, sustained or worsened at a later time point using exclusive categories and as observed analyses. Similar shift analysis on DAS28-CRP derived criteria were performed in 4 exclusive categories extrapolated from rheumatoid arthritis: high, moderate, low disease activity (HDA, MDA, LDA) or remission (REM) only. 4 Results: In total, 86/100 (86%) and 76/100 (76%) pts in the secukinumab 300 and 150mg groups, respectively, completed the 104-wk treatment. Of which, 73/70 and 81/75 pts in secukinumab 300/150mg were eligible for ACR and DAS28-CRP shift analysis, respectively, from Wk 24 to 104. Baseline demographics and clinical characteristics were balanced across the two dose groups. 2, 3 Most secukinumab-treated pts who achieved at least an ACR20, 50 or 70 response and Psoriasis Area and Severity Index (PASI) 75 or 90 response at Wk 24, improved or sustained their response at Wk 104 (Figure, data not shown for PASI response). Similarly, a majority of pts who were in the MDA, LDA or REM category at Wk 24 sustained or improved their disease status related to DAS28-CRP score at Wk 104 (Figure). Conclusions: In this post-hoc analysis, a majority of secukinumab-treated pts who achieved at least ACR20 and PASI 75 response or at least MDA at Wk 24 sustained or improved their ACR and PASI responses or sustained or reduced their disease status at Wk 104. Numerically higher sustained response and LDA or REM rate was observed for secukinumab 300mg, thereby extending the sustainability of response and lowering the disease activity that has been previously reported at group level. 2, 3 References: Gossec L, et al. Ann Rheum Dis 2016;75:499–510. McInnes IB, et al. Lancet 2015;386:1137–46. McInnes IB, et al. Arthritis Rheumatol 2016;68;abstract: 2757. Wells G, et al. Ann Rheum Dis 2009;68:954–60. Disclosure of Interest: P. Emery Consultant for: AbbVie, BMS, Merck, Novartis, Pfizer, Roche, UCB, I. McInnes Consultant for: Novartis, Amgen, Janssen, BMS, Pfizer, UCB, Abbvie, Celgene, Lilly, P. Mease Grant/research support from: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Crescendo, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Covagen, Crescendo, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Biogen Idec, BMS, Crescendo, Janssen, Lilly, Pfizer, UCB, M. Schiff Consultant for: Abbvie, BMS, Lilly, J&J, Speakers bureau: Abbvie, L. Pricop Shareholder of: Novartis, Employee of: Novartis, S. Shen Employee of: Novartis, Z. Wang Employee of: Novartis, C. Gaillez Shareholder of: Novartis, BMS, Employee of: Novartis